Domain Transform for Spherical Geometry Images - Gastal , Eduardo S. L.; Kersting, Felipe Einsfeld (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
This work presents the Domain Transform for Spherical Geometry Images (DT-SGIM): a filter designed for smoothing triangle meshes represented as spherical geometry images (SGIM) and, at the same time, preserving the meshes' important curvatures. It is based on the domain transform filter (DT), a high-performance, real-time algorithm for edge-aware smoothing of color images. Our main contribution is the extension of the DT filter to the SGIM domain, resulting in the first method specifically designed for filtering 3-D objects represented by SGIMs, as well as the first demonstration of a domain transform-based filter applied to the problem of polygonal mesh filtering.